The Prototype of the Stakeholder Collaboration Model in the Management of Homestay in the Tourism Village of Kembang Kuning - Herman Herman; Ayu Gardenia Lantang; Siti Lathifah (Budapest International Research and Critics University, 2022)
This study seeks to develop a prototype model of stakeholder collaboration related to the management of homestays in the Kembang Kuning Tourism Village. The reason behind this research is the existence of homestays and the community as managers who feel the impact of the Covid – 19 Pandemic - One way that can be taken to get out and survive in the Covid-19 Pandemic is by collaboration. This study aims to a) identify the stakeholders who play a role in the management of homestays in the Kembang Kuning Tourism Village; b) analyze the form of roles given to homestays in Kembang Kuning Tourism Village, and c) design the prototype of the Stakeholder Collaboration Model that can be given to the manager of the Homestay in the Kembang Kuning Tourism Village. The method used in this research is descriptive with a qualitative approach, and data collection methods used are interviews, FGDs, and documentation. The results of this study are that there are 18 stakeholders involved in the management of the Homestay. However, of the 18 existing stakeholders, only eight stakeholders play an optimal and sustainable role. The rest is still not optimal and not sustainable. The design of the formed model shows that there is still a lack of sense of responsibility, less active communication links, and the existence of unequal understanding between stakeholders regarding the vision and mission of homestay management in Kembang Kuning Tourism Village.